Misuse of Limited Stay Permits (ITAS) for Foreign Investors from the Perspective of National Resilience: A Case Study of the Special Region of Jakarta in 2025 - Mochamad Irsyad Makrufi; Stanislaus Riyanta (Eduvest - Journal of Universal Studies, 2026)
The increasing flow of foreign investment and the relative ease of obtaining Limited Stay Permits for Foreign Investors (ITAS Investor) generate significant economic benefits, yet they also open up vulnerabilities to residence-permit misuse that can affect investment quality, security, and national resilience. This study analyzes the patterns of Limited Stay Permits for Foreign Investor misuse in the Special Region of Jakarta, evaluates the immigration supervision system currently in place, and formulates an intelligence-based supervision strategy framed as a competitive early-warning mechanism. It uses a qualitative approach built on a single-case design with embedded units of analysis, following Yin. Data were collected through in-depth interviews with sixteen key informants, document study, and immigration enforcement records, then analyzed thematically through source triangulation. The findings show that Limited Stay Permits for Foreign Investor misuse follows a technical-organizational pattern marked by a gap between administrative formality and actual business realization, together with a socio-functional pattern involving investors, sponsoring companies, agents, and intermediary networks in activities inconsistent with the permit granted. The supervision system is supported by partial document integration, field inspections, foreigners supervision team, and joint operations, yet it still struggles with weak substantive verification and reactive post-issuance monitoring. The study proposes a competitive early-warning model built around risk identification, intelligence monitoring, and management action, aimed at safeguarding investment quality and strengthening Indonesia's national resilience.